Conditions for Considering the Financial Market as an Islamic Market - Abu- mounes, Raed Nasri; Khadidja, Chouchane (Dirasat: Shari’a and Law Sciences, 2020)
The establishment of the Islamic financial market is one of the major challenges in the way of applying the theories of Islamic economics, and the research into professional and technical standards and conditions as well as the legitimate conditions for the establishment of this market is one of the most important problems that still need to provide clear and detailed visions, in order to provide financial models for the management of Islamic financial markets, in a way that combines economic profitability and professional efficiency. This research addresses the most important conditions related to the establishment of the Islamic financial market, such as: disclosure, transparency, freedom from fraud and injustice, and others, through the definition of these standards and conditions and indicate what they are and their components. This study aims to show the extent to which an efficient and economically profitable Islamic financial market can be achieved if its basic conditions are met. The study concluded that the establishment of an Islamic financial market characterized by legitimacy and economic efficiency requires the achievement of an integrated set of legitimate and professional conditions. Accordingly, the study recommends the need to allocate the conditions of establishing the Islamic financial market with specialized studies as a way to build models and Islamic financial instruments that meet the needs and purposes of all dealers in the market within the framework of Sharia requirements.